2010
DOI: 10.1143/jjap.49.08jb03
|View full text |Cite
|
Sign up to set email alerts
|

Etching Characteristics and Mechanism of ZnO and Ga-Doped ZnO Thin Films in Inductively Coupled HBr/Ar/CHF3 Plasma

Abstract: A phonon side-band occurs at about 490 cm-1 in the vibronic structure of 4f-5d transitions of Ce3f in CaFz. This frequency is greater than the highest vibrational frequency of the CaFz lattice. It is suggested that the side-band is due to a local mode arising from vibration of the eight nearest fluorine neighbours of the Ce3+ ion, and that the high frequency is a consequence of increased force constants at the impurity site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…11,12) Also, in our previous work, we investigated the etching characteristics and mechanisms of both ZnO and Ga-doped ZnO (GZO) thin films with the HBr-based gas chemistries. 13,14) We found that the ZnO etch rate is comparable to that obtained using chlorine-based chemistries, while the etch process occurs in the reaction-rate-limited etch regime with Br atoms acting as the main chemically active species. As for the Inand Ga-doped ZnO (IGZO) thin films, there are only few reports on this issue.…”
Section: Introductionmentioning
confidence: 72%
“…11,12) Also, in our previous work, we investigated the etching characteristics and mechanisms of both ZnO and Ga-doped ZnO (GZO) thin films with the HBr-based gas chemistries. 13,14) We found that the ZnO etch rate is comparable to that obtained using chlorine-based chemistries, while the etch process occurs in the reaction-rate-limited etch regime with Br atoms acting as the main chemically active species. As for the Inand Ga-doped ZnO (IGZO) thin films, there are only few reports on this issue.…”
Section: Introductionmentioning
confidence: 72%
“…In our previous work, deep etching with HBr/N 2 /CH 3 F-based gas plasma was successfully demonstrated to fabricate the holes in poly-Si/SiO 2 stacks. [14][15][16][17][18][19][20][21][22][23][24] The vertical and deep hole profile was obtained by a combination of N 2 addition and the adjustment of the substrate temperature to under 20 °C. To understand the mechanism of the deep etching in our HBr/N 2 /CH 3 F-based gas chemistry, the surface composition was analyzed using blanket wafers and pattern samples.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] The HBr and fluorocarbonbased gases were mixed to achieve uniform etching rates for both poly-Si and SiO 2 and thus obtain smooth side walls in the etched holes. [18][19][20][21][22] Furthermore, nitrogen gas was added to the etching gas, and the substrate temperature was adjusted to obtain a vertical hole profile. A film consisting of a fluorocarbon polymer was deposited on the substrate when the substrate was not bombarded with ions from the plasma, and a mixing layer (2-3 nm thick) containing carbon, fluorine, nitrogen, bromine, and substrate material formed when the substrate was bombarded with ions.…”
Section: Introductionmentioning
confidence: 99%